3x+1+2x*3x-18x-27
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,=27-5\sqrt{3x}\\ b,=3\sqrt{2x}-10\sqrt{2x}+21\sqrt{2x}+28=14\sqrt{2x}+28\)
\(a,=27-5\sqrt{3x}\\ b,=3\sqrt{2x}-10\sqrt{2x}+21\sqrt{2x}+28=14\sqrt{2x}+28\)
\(2x^2-8x=-8\)
\(2x^2-8x+8=0\)
\(2\left(x^2-4x+4\right)=0\)
\(2\left(x-2\right)^2=0\)
\(\Rightarrow x-2=0\)
\(x=2\)
\(-3x^2+18x-27=0\)
\(-3\left(x^2-6x+9\right)=0\)
\(-3\left(x-3\right)^2=0\)
\(\Rightarrow x-3=0\)
\(x=3\)
\(2x^2-8x=-8\)
\(\Leftrightarrow2\left(x^2-4x+4\right)=0\)
\(\Leftrightarrow2\left(x^2+2x2+2^2\right)=0\)
\(\Leftrightarrow2\left(x-2\right)^2=0\)
\(\Rightarrow x=2\)
1: \(\dfrac{2x^3+11x^2+18x-3}{2x+3}\)
\(=\dfrac{2x^3+3x^2+8x^2+12x+6x+9-12}{2x+3}\)
\(=x^2+4x+3-\dfrac{12}{2x+3}\)
7x2 - 28 = 7(x2 - 4) = 7(x - 2)(x + 2)
2x3 + 3x2 - 18x - 27 = x2(2x + 3) - 9(2x + 3) = (2x + 3)(x2 - 9) = (2x + 3)(x - 3)(x + 3)
\(a,\left(3x+1\right)\left(3x-1\right)-\left(18x^3+5x^2-2x\right):2x\\ =\left(9x^2-1\right)-\left(9x^2+\dfrac{5}{2}x-1\right)\\ =9x^2-1-9x^2-\dfrac{5}{2}x+1=\dfrac{5}{2}x\)
\(b,3x\left(x-2021\right)-x+2021=0\\ \Rightarrow b,3x\left(x-2021\right)-\left(x-2021\right)=0\\ \Rightarrow\left(x-2021\right)\left(3x-1\right)=0\\ \Rightarrow\left[{}\begin{matrix}x=2021\\x=\dfrac{1}{3}\end{matrix}\right.\)
\(=3^x\cdot3+2x\cdot3^x-9\left(2x+3\right)\)
=3^x(2x+3)-9(2x+3)
=(2x+3)(3^x-9)